Scalable, Highly Pure, and Diameter‐Sorted Boron Nitride Nanotube by Aqueous Polymer Two‐Phase Extraction. Issue 4 (27th January 2023) - Ko, Jaehyoung; Kim, Daeun; Sim, Giho; Moon, Se Youn; Lee, Sang Seok; Jang, Se Gyu; Ahn, Seokhoon; Im, Sung Gap; Joo, Yongho
Abstract: Boron nitride nanotube (BNNT) has attracted recent attention owing to its exceptional material properties; yet, practical implementation in real‐life applications has been elusive, mainly due to the purity issues associated with its large‐scale synthesis. Although different purification methods have been discussed so far, there lacks a scalable solution method in the community. In this work, a simple, high‐throughput, and scalable purification of BNNT is reported via modification of an established sorting technique, aqueous polymer two‐phase extraction. A complete partition mapping of the boron nitride species is established, which enables the segregation of the highly pure BNNT with a major impurity removal efficiency of > 98%. A successful scaling up of the process is illustrated and provides solid evidence of its diameter sorting behavior. Last, towards its macroscopic assemblies, a liquid crystal of the purified BNNT is demonstrated. The effort toward large‐scale solution purification of BNNT is believed to contribute significantly to the macroscopic realization of its exceptional properties in the near future. Abstract : A scalable solution protocol for isolating boron nitride nanotube (BNNT) from its large‐scale synthetic mixture is presented. A comprehensive understanding of the partition behavior of the boron nitride species is described. Along with the diameter sorting capability of the protocol, macroscopic realization of BNNT's intrinsic property through the formation of its liquid crystal is demonstrated.